Algorithm-based approach to hypervascular pancreatic lesions - Leow, Kheng Song (2021)
Incidental pancreatic lesions are increasingly being detected due to the increasing use of cross-sectional imaging such as computed tomography (CT) and magnetic resonance (MR) imaging. These pancreatic lesions can be broadly categorised into hypervascular and hypovascular lesions by comparing the degree of lesion enhancement to the background pancreatic parenchymal enhancement. For practicality, we define pancreatic lesions as hypervascular when they show enhancement greater or equal to that of the pancreatic parenchyma on either CT or MR imaging vis-a-vis hypovascular lesions, which characteristically enhance less than the background pancreatic parenchyma. Hypovascular lesions have been widely described, including ductal adenocarcinoma and chronic focal pancreatitis.(1) A few prior published reviews related to hypervascular pancreatic masses have focused on the differential entities or their malignant potential.(2,3) To the best of our knowledge, there is a lack of an algorithm-based approach that enables general radiologists to prospectively differentiate the various hypervascular pancreatic lesions, as presented in this pictorial essay. We further discuss the pertinent radiologic pathologic features of each differential diagnosis and illustrate them using individual case examples.